High-sensitivity HBV DNA test for the diagnosis of occult HBV infection: commonly used but not reliable - Wang, Chengwei; Xue, Rongrong; Wang, Xinru; Xiao, Li; Xian, Jianchun (Frontiers in Cellular and Infection Microbiology, 2023)
[Abstract] Occult hepatitis B virus (HBV) infection (OBI) is a condition in which replication-competent viral DNA is detected in the liver (with detectable or undetectable HBV DNA in serum) of individuals testing negative for HBV surface antigen (HBsAg). It is a risk factor for transfusion or transplant transmission, reactivation after immunosuppression or chemotherapy, and progression of chronic liver disease and hepatocarcinogenesis. The long-term stable presence of covalently closed circular DNA (cccDNA), which is fully replicative in the nucleus of infected hepatocytes is the molecular basis for the formation of OBI. HBV genome in liver tissue, HBV DNA and anti-HBc test in serum are the gold standard, common method and alternative markers for OBI diagnosis, respectively. Due to the stability of cccDNA and the long half-life of hepatocytes, the existence of OBI is extensive and prolonged. The low and/or intermittent replication of HBV in OBI patients, the limitations of the sensitivity of serological tests, and the non-standardized and invasive nature of liver histology render the "commonly used" serological tests are unreliable and the "gold standard" liver histology is impractical, thus the findings from studies on the formation, diagnosis and transplantation or transfusion transmission of HBV in OBI strongly suggest that the "alternative" marker, the anti-HBc test, may be the most reliable and practical approach for OBI diagnosis.